Reformationsmandat für den Thurgau 1530 - Wälchli, Philipp (Zwingliana, 2012)
In 1530, Philipp Brunner, the governor in the dependent territory of Thurgau enacted a church ordinance introducing reform. Brunner did so by consent of Zurich, which was one of the governing states. However, the strong opposition of the other governing states, resting Catholic, made the ordinance ineffective, for the most part, and Thurgau remained bi-confessional. A short analysis of this church ordinance, critically edited here for the first time, is astonishing because only six of thirteen chapters are derived from the fundamental church ordinance of Zurich, enacted in 1530, while seven are excerpts of the Basle church ordinance of 1529. Since Zurich did not have a church ordinance covering all matters of interest, but Basle did, the two primary church ordinances from both cities were combined. Thus, the Thurgau Church Ordinance of 1530 is an early and important testimony to the effects and reception of the church ordinances from both cities.